The incidence of hypoxemia due to malposition of double lumen endotracheal tube during one lung ventilation - Al-hassani, Osamah H. (Journal of the Faculty of Medicine Baghdad, 2014)
Fac Med Baghdad 2014; Vol.56, No.2 Received: Jan., 2014 Accepted March. 2014 Background: Oxygenation during one lung ventilation (OLV) can be affected by positioning of Double lumen endobronchial tube (DLT). Mal position can occurs following intubation and moving the patient to the lateral decubitus position. Objectives: To study the relation of hypoxemia to mal position of double lumen endo bronchial tube after patient positioning in lateral decubitus position and during one lung ventilation. The use of fiber-optic scope in detecting the mal position and correcting it is illustrated. Methods: A study of 80 patients with ASA physical status I-II patients about to have elective thoracic operations. The intubation of the trachea was done with a left sided DLT, then checked clinically by auscultation and with use of fiber-optic scope and this done after patient positioning and during OLV. Oxygen saturation was measured by non invasive pulse oxy meter. IF oxygen saturation below 92 % (10.6kpa) 80 mmHg is detected, the DLT position must be checked and positive end expiratory pressure (PEEP), oxygen insufflations or (continuous positive airway pressure). CPAP or total lung ventilation (TLV) was tried if needed. Result: Misplacement of DLT was found in 28 patients (35%) after patient positioning and in 24 patients (30%) during OLV. Patients who had malpostion of DLT after placing the patients in lateral decubitus position had a greater incidence of malposition of DLT in OLV (64%). The application PEEP to the dependent lung, CPAP or oxygen insufflations to the upper lung or brief periods of TLV were applied in 28 patients. Conclusion: Patients who have mal position of DLT in lateral position had more incidence of hypoxemia and DLT mal position in OLV and mostly require intervention with use of fiber-optic bronchoscopy which is mandatory for detecting and correcting the mal position.